1984
DOI: 10.1099/0022-1317-65-3-617
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Biological Characterization of Mouse LM Fibroblast Variants Resistant to the Cytotoxicity of Polyriboinosinic{middle dot}Polyribocytidylic Acid after Interferon Treatment

Abstract: SUMMARYMouse LM fibroblasts growing continuously in the absence of serum have an increased sensitivity to the cytotoxicity of poly(rI).poly(rC) after interferon (IFN) exposure. This has allowed the isolation by an enrichment procedure of several independent and stable variant clones (IFN + I. C) g which are resistant to such a treatment. One of the resistant variants has been more extensively characterized as far as IFN action and IFN production are concerned. It behaves identically to the wildtype parent exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…1 (b) shows that the toxic effect of poly(rI).poly(rC) was not improved above 2 ~tg/ml. Previous experiments had already demonstrated that IFN-treatment allowed effective lysis at 1000 units/ml and above (Faure et al, 1984). In most experiments described here, poly(rI), poly(rC) was used at 5/.tg/ml and IFN at 1000 units/ml.…”
Section: Lysis Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 (b) shows that the toxic effect of poly(rI).poly(rC) was not improved above 2 ~tg/ml. Previous experiments had already demonstrated that IFN-treatment allowed effective lysis at 1000 units/ml and above (Faure et al, 1984). In most experiments described here, poly(rI), poly(rC) was used at 5/.tg/ml and IFN at 1000 units/ml.…”
Section: Lysis Conditionsmentioning
confidence: 99%
“…The experimental conditions leading to lysis induced by poly(rI).poly(rC) on IFN-treated cells have been described previously (Faure et al, 1984). Long term exposure of IFN-treated cells to poly(rI), poly(rC) results in lysis of up to 90~ of the cells.…”
Section: Lysis Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would explain the incomplete neutralization by IFN antibodies we observed. However, our own experiments (Faure et al, 1984;P. G. Milhaud, M. Silhol, T. Salehzada & B. Lebleu, unpublished results) at least do not favour an involvement of cell cytotoxicity of microinjected poly(rI).poly(rC) apart from the low (< 10~) cell mortality inherent in the microinjection procedure itself.…”
Section: Antiviral Activity Of Microinjected Poly(rl)poly(rc) Is Neumentioning
confidence: 90%
“…Studies by our group on the toxicity of poly(rI), poly(rC) for IFN-treated murine cells (Faure et al, 1984;P. G. Milhaud, M. Silhol, T. Salehzada & B. Lebleu, unpublished) strongly suggest the involvement of fluid-phase endocytosis.…”
Section: Discussionmentioning
confidence: 99%